2008
DOI: 10.1093/hmg/ddn219
|View full text |Cite
|
Sign up to set email alerts
|

Tdrd3 is a novel stress granule-associated protein interacting with the Fragile-X syndrome protein FMRP

Abstract: Tudor domains are widespread among proteins involved in RNA metabolism, but only in a few cases their cellular function has been analyzed in detail. Here, we report on the characterization of the ubiquitously expressed Tudor domain containing protein Tdrd3. Apart from its Tudor domain, we show that Tdrd3 possesses an oligosaccharide/nucleotide binding fold (OB-fold) and an ubiquitin associated domain capable of binding tetra-ubiquitin. A set of biochemical experiments revealed an interaction of Tdrd3 with FMRP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
95
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 39 publications
5
95
0
2
Order By: Relevance
“…The human fragile X mental retardation proteins FMRP and FXR1 localize to mammalian SGs (Mazroui et al 2002;Linder et al 2008). We assessed the localization of the Drosophila homolog FMR1 in stressed cells, and found that FMR1 and poly(A) + RNA are co-localized in cytoplasmic granules after exposure to arsenite or 40°C heat shock ( Fig.…”
Section: Drosophila Stress-induced Poly(a)mentioning
confidence: 99%
“…The human fragile X mental retardation proteins FMRP and FXR1 localize to mammalian SGs (Mazroui et al 2002;Linder et al 2008). We assessed the localization of the Drosophila homolog FMR1 in stressed cells, and found that FMR1 and poly(A) + RNA are co-localized in cytoplasmic granules after exposure to arsenite or 40°C heat shock ( Fig.…”
Section: Drosophila Stress-induced Poly(a)mentioning
confidence: 99%
“…Mutations in MSH5 (Signals #15a and #15b) have been associated with various human diseases including POI 13 . In addition, TDRD3 (Signal #28) is a primary binding partner of FMR1 in which triplet repeat premutations are a risk factor for POI 14 .…”
Section: Anm Snps Enriched In Known Poi Genesmentioning
confidence: 99%
“…Western blot analyses were performed as described previously (Otter et al 2007), using appropriate antibodies. Immunocytochemistry and stress treatment were carried out as depicted in Linder et al (2008).…”
Section: Immunological Proceduresmentioning
confidence: 99%